Combined antegrade and retrograde thoracic duct embolization for complete transection of the thoracic duct - Drabkin, Michael (Radiol Case Rep, 2020)
Chylothorax is an uncommon complication after thoracoabdominal surgery and is typically due to injury of the thoracic duct (TD) or one of its tributaries. Patients who fail conservative management benefit from thoracic duct embolization (TDE). TDE is a percutaneous technique that includes pedal or intranodal lymphangiography, transabdominal catheterization of the TD, and glue embolization of the TD. Alternative access to the TD can be achieved via retrograde transvenous approach or direct US-guided puncture in the left neck followed by TDE. This case involves chylothorax in a 58-year-old male due to disruption of the main TD during esophagectomy, resulting in disjointed leaks from 2 separate areas related to a single complex injury. Lymphangiography and embolization via both transcervical and transabdominal approaches were performed to stop the leak.